Harnessing the phytochemical potential of Curcuma angustifolia rhizomes: A comprehensive evaluation of antibacterial and antioxidant properties: Phytochemical potential of Curcuma angustifolia - Rabita, N; Palanisamy, K (Journal of Spices and Aromatic Crops, 2025)
Herbaceous perennial Curcuma angustifolia Roxb. has been traditionally utilized in folk medicine for a variety of purposes. The objective of the current study was to assess the phytochemical, antimicrobial, and antioxidant qualities of Curcuma angustifolia plant rhizomes. Based on preliminary phytochemical investigations, the chemical classes found in the extracts included flavonoids, alkaloids, steroids, phenols, saponins, terpenoids, cardiac glycosides, and tannins. The findings suggested that the plant phytochemical qualities could be used to treat a variety of illnesses. With the agar-well diffusion method, the antimicrobial effectiveness of the plant extracts was evaluated against both clinical isolates and standard strains of certain bacteria. The extracts demonstrated an inhibitory impact on both gram-positive and gram-negative bacteria. Gram-positive bacteria like Staphylococcus aureus had the largest zone of inhibition, whereas gram-negative bacteria like Klebsiella pneumoniae had the lowest. The DPPH radical scavenging assay was used to assess the extracts antioxidant properties. Antioxidant activity increased with extract concentration. Since it has antibacterial and antioxidant qualities, it is useful for treating a range of illnesses, enhancing immunity, and combating harmful bacteria that infect humans.